PELATIHAN VISUALISASI MOLEKUL KIMIA DENGAN SOFTWARE CHEMSKETCH UNTUK SISWA TINGKAT SEKOLAH MENENGAH ATAS - Esti Mulatsari; Esti Mumpuni; Liliek Nurhidayati; Agus Purwanggana; Diah Kartika Pratami (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
Senior High School (SMA) has a very broad scientific scope, one of which is chemistry. In chemistry, it presents the processes, chemical notations, types, and arrangements of matter. Chemical processes can be written in a concise form, such as a reaction equation, without eliminating the microscopic and macroscopic aspects that occur in the chemical process. This equation for the reaction is a symbolic aspect of chemistry. All the substances involved in the equation of the reaction are also symbolic aspects of chemistry. In other words, chemical formulas, such as atomic symbols, element symbols, compound symbols or formulas, all of these are symbolic aspects of chemistry. This symbolic aspect is of great importance in chemistry. Training on the use of ChemSketch software is very important for high school students, especially science majors, as an enrichment for chemistry subjects and improves skills in presenting chemical data in order to improve the quality of graduates. ChemSketch software provides process symbols, chemical notations, types, arrangement of materials, and several image representations of various laboratory tools, which are quite easy to use. Training on the use of ChemSketch for SMA N 13 Depok students has been enthusiastically carried out online, the material is relevant to chemistry subject matter, easy to accept and the delivery of the material is quite interesting.